Imperative of Entrepreneurship Education for University Students: The Case Study of University of Ibadan - Olubukola G. Yomi-Akinola; Adeolu A. Adedapo (Unilag Journal of Humanities, 2019)
The renewed interest in the study and practice of entrepreneurship in the 21st century isdue to its potency to create business, boost productivity, and increase wealth, as well asits capacity to effect positive change in market or industry structure in particular and thesociety in general. Entrepreneurship education became compulsory for allundergraduates of Higher Educational Institutions in Nigeria effective from 2007/2008academic session with a view to re-orientating graduates towards entrepreneurial selfefficacy, value creation and self-employment. This study assesses the beneficial impact ofentrepreneurship education on University of Ibadan (UI) students. The research deploysboth theoretical and conceptual frameworks of Entrepreneurship, and follows the trendsin entrepreneurship value and development. A population of all students who have passedthrough GES 301, both GES 301 and ETR 301, or are doing M.Sc. in Entrepreneurshipwas involved. Samples were drawn using the purposive sampling technique via an onlinesurvey, created through Google Forms. A sample size of one hundred and two wasinvolved. The research findings justify the inclusion of entrepreneurship education in thecurricula of UI.